The effect of the aging period on the martensitic transformation and kinetic characteristic of at % Cu68.09Al26.1Ni1.54Den4.27 shape memory alloy - Ozkul, Iskender; Canbay, C. Aksu; Aladag, Faruk; Aldas, Kemal (Allerton Press Inc, 2017)
In this work, the effect of aging period on the characteristic transformation temperatures, thermodynamic parameters and structural variations of CuAlNiMn shape memory alloys were investigated. Aging was performed at above the austenite finish temperature of the un-aged specimen (120A degrees C) for six different retention times, namely 1h, 2h, 3h, 4h, 5h and 6h. The changes in the transformation temperatures were examined by differential scanning calorimetry at different heating/cooling rates. The aging period was found to have an effect on the characteristic austenite and martensite transformation temperatures and thermodynamic parameters such as the enthalpy and entropy of alloys. High-temperature order-disorder phase transitions were determined using a differential thermal analysis, which showed that all the un-aged and aged specimens had an A2 -> B2, B2 -> L2(1) and an L2(1) -> 9R, 18R transition. The structural analysis of the un-aged and aged specimens was performed through X-ray diffraction measurements at room temperature. The intensities of the diffraction peaks varied according to the aging time.
Keywords: aging; shape memory effect; phase transition; structure